Prescribing databases can be used to monitor trends in opioid analgesic prescribing in Australia - Samantha A. Hollingworth; Martyn Symons; Mohsina Khatun; Bill Loveday; Sue Ballantyne; Wayne D. Hall; Jake M. Najman (Elsevier, 2013)
Abstract Objective: There has been increased use of prescription opioid analgesics in Australia in the past 20 years with increasing evidence of related problems. A number of data sources collect information about the dispensed prescribing for opioid medications, but little is known about the extent to which these data sources agree on levels of opioid prescribing. Methods: In Queensland, all opioid prescriptions (S8 prescriptions) dispensed by community pharmacies must be submitted to the Drugs of Dependence Unit (DDU). This potentially comprises a 'gold standard' against which other data sources may be judged. There are two national data sources: the Pharmaceutical Benefits Schedule (PBS) for all medications subsidised by government; and an annual national survey of representative pharmacies, which assesses non‐subsidised opioid prescribing. We examined the agreement between these data sources. Results: The three data sources provided consistent estimates of use over time. The correlations between different data sources were high for most opioid analgesics. There was a substantial (60%) increase in the dispensed use of opioid analgesics and a 180% increase in the dispensed use of oxycodone over the period 2002-2009. Tramadol was the most used opioid‐like medication. Conclusions: Since 2002 different data sources reveal similar trends, namely a substantial increase in the prescribing of opioid medications. With few exceptions, the conclusions derived from using any of these data sources were similar. Implications: Improved access to PBS data for relevant stakeholders could provide an efficient and cost‐effective way to monitor use of prescription opioid analgesics.